2010
DOI: 10.2984/64.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographic Breaks in Vanuatu, A Nascent Oceanic Archipelago

Abstract: The study of distinct biogeographic demarcations has played a pivotal role in our understanding processes responsible for patterns of species distributions and, importantly, the role of geologic processes in promoting biotic diversification. Biogeographic barriers such as Wallace's line have been shown to be the result of old geologic processes shaping ancient faunal or floral diversification events. Based on distributions of birds, bats, reptiles, plants, and invertebrates we identify a distinct biogeographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…One would be located on the Western border of Vanuatu, colonising both western Vanuatu locations and New Caledonia using the south Vanuatu and the north and south Caledonian jets (Cillauren et al 2001). It has indeed been shown that there is strong population connectivity between New Caledonia and Vanuatu due to ocean currents (Treml et al 2008;Hamilton et al 2010). The other larval pool would be confined to the "central" location of Vanuatu, representing a sort of internal "sea", at the centre of the archipelago, less penetrable by main ocean currents (Cillauren et al 2001).…”
Section: Discussionmentioning
confidence: 97%
“…One would be located on the Western border of Vanuatu, colonising both western Vanuatu locations and New Caledonia using the south Vanuatu and the north and south Caledonian jets (Cillauren et al 2001). It has indeed been shown that there is strong population connectivity between New Caledonia and Vanuatu due to ocean currents (Treml et al 2008;Hamilton et al 2010). The other larval pool would be confined to the "central" location of Vanuatu, representing a sort of internal "sea", at the centre of the archipelago, less penetrable by main ocean currents (Cillauren et al 2001).…”
Section: Discussionmentioning
confidence: 97%
“…As noted by Steadman (2006a) and Hamilton et al (2010) the majority of birds found in Vanuatu, especially columbids, are widespread, with most shared with the Solomons or areas of Melanesia to the west such as the Bismarks. Only 12 of the 62 taxa of land and freshwater birds Steadman (2006a) listed for Vanuatu were considered endemic, three of which were columbids (i.e., Ptilinopus tannen sis, Ducula bakeri, and Gallicolumba ferruginea).…”
Section: Columbid Biogeography and A Melanesian Tongan Linkmentioning
confidence: 99%
“…Only three other bird species, in the widespread genera Aythya, Circus, and Artamus, have distributions in both areas, but all range over a much greater geographic area including into Australia. This lack of overlap between the faunas of Vanuatu and New Caledonia contributes to the biotic break long recognized between these landmasses (Gibbons 1985, Bauer 1988, Hamilton et al 2010 ( Hamilton et al 2010), which places Efate with all more northern islands. It was based on diverse data for plants, invertebrates, and vertebrates, particularly squamates.…”
Section: Columbid Biogeography and A Melanesian Tongan Linkmentioning
confidence: 99%
See 2 more Smart Citations